DEVELOPING ENGLISH LANGUAGE TEACHING MATERIALS BASED ON BANYUWANGI LOCAL WISDOM FOR EIGHTH GRADERS OF SMPN 3 BANYUWANGI - Tri Mulyati -; Zainur Rohman; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
One of the most crucial aspects of teaching and learning is the learning material. As a result, teachers must take a variety of steps to ensure that learning materials are successfully presented and that students are happy and focused during teaching and learning activities. This study aims to develop a recount text reading materials based on Banyuwangi local wisdoms for VIII E students of SMPN 3 Banyuwangi and know its feasibility according to material/culture expert and English teacher. This study adopts research and development design based on its aims. The development stages partially taken are need analysis, designing, small group trial, and first revision. The results of development show that the product gained a very feasible level in common based on expert and English teacher’s validation. Therefore, it can be concluded that recount text reading materials based on Banyuwangi local wisdoms can be used in English learning activities in class VIII of SMPN 3 Banyuwangi.